The feminist attributes of leadership in service to community: Life history interviews with 12 exemplary Canadian women age 70 plus. - Way, A. Rosanne. (University of Ottawa (Canada), 2002)
This exploratory study addressed two research questions: What are the perspectives on patterns and themes in the life development of exemplary Canadian women over the age of 70 who have been active in leadership roles in volunteer and/or paid work in their communities? Do these patterns and themes support the concept of the Feminist Attributes of Leadership (caring, courage, collaboration, vision, and intuition) within a relational leadership context as identified by Regan and Brooks (1995)? Following a qualitative research design with twelve participants who were leading active, exemplary lives in late adulthood, data were collected in three phases: (1) Individual interviews designed to elicit recollections of leadership experience and a brief life history. (2) Focus groups in which participants discussed their leadership experience and involvement in pro-social activities. (3) A questionnaire completed by someone selected by the participants and able to offer another perspective on their lives and leadership contribution. Analysis revealed that the women were characterized by the descriptors wise, courageous, and action-oriented. Each in her own way, given her varied opportunities and gifts, had lived the well-lived life. Each had made an exemplary contribution to her community over a period of many years. Each was in the process of successfully resolving Erikson's eighth psycho-social crisis, integrity vs. despair (Erikson, 1982). Support was found for Regan & Brooks (1995) Feminist Attributes of Leadership within a Relational Leadership style. A new model, The Exemplary Leadership Model, was created to summarize the findings. It presents a perspective on leadership featuring the descriptors wise, courageous, and action-oriented. The "L" of Exemplary Leadership is firmly embedded within the "C" of Caring, and grounded on a three tier foundation. Social conscience, arising out of love, empathy, sympathy, and identity is the upper tier of the model's foundation. The first tier consists of family, community, culture, and social connectedness. Results of the study have implications for those who work with the elderly and for those involved in education, leadership, community activism, and volunteerism.
Keywords: Gerontology.